A cost-effective compressed air generation for manufacturing using modified microturbines. (25th August 2016) - Eret, Petr
Highlights: A new cost-effective way of compressed air generation for manufacturing in SME is proposed. The approach is based on a modified microturbine configuration. Thermodynamic and life cycle analyses are presented and economic benefit is demonstrated. Abstract: Compressed air is an irreplaceable energy source for some manufacturing processes, and is also common in applications even when there are alternatives. As a result, compressed air is a key utility in manufacturing industry, but unfortunately the cost of compressed air production is one of the most expensive processes in a manufacturing facility. In order to reduce the compressed air generation cost an unconventional way using a microturbine configuration is proposed. The concept is based on an extraction of a certain amount of compressed air from/after the compressor with the residual air flowing to the turbine to produce sufficient back power to drive the compressor. A thermodynamic and life cycle analysis are presented for several system variations, including a simple cycle without a recuperator and a complex configuration with an intercooler, recuperator and reheating. The study is based on the typical requirements (i.e. quantity, pressure) for a small to medium sized industrial compressed air system. The analysis is focused on the North American market due to the low price of natural gas. The lowest life cycle cost alternative is represented by a microturbine concept with a recuperator, air extraction after partial compression, intercooler and aftercooler. A comparison of an electric motor and conventional microturbine prime movers demonstrates the economic benefit of the proposed compressed air generation method, for the design parameters and utility prices considered.